Implementation of an Integrated System for Surveillance, Monitoring and Security in a Compartment using the Internet of Things. (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Security can be defined as the degree of resistance to, and resilience against, various forms of harm. It influences all facets of human existence, with infrastructure serving as a critical domain requiring robust security measures. Broadly speaking, security denotes a state of being free from threats and dangers, encompassing the protection of individuals and organizations against criminal activities such as terrorism, kidnapping, theft, piracy, and espionage. In the context of public transportation, particularly within train compartments, security is paramount to ensuring the safety and well-being of both passengers and cargo. In contemporary society, the lack of sufficient security measures on trains presents a significant concern for commuters. Issues such as theft, harassment, kidnapping, violence, and espionage have become increasingly prevalent among train users. The inadequacies of security personnel, coupled with the ineffective implementation of safety protocols, have exacerbated these challenges. Historically, the security framework aboard trains has been limited to basic measures such as lockable doors and windows, emergency alarm systems, and routine patrols conducted by train staff. The imperative for enhanced security and safety across both public and private sectors cannot be overstated. The development of various technological devices designed for the purposes of security has contributed substantially to improved safety conditions. Notably, the concept of safety extends beyond the mere physical protection of an organization to encompass an integrated approach to security.